PENGARUH MODEL REALISTIC MATHEMATICS EDUCATION TERHADAP KEMAMPUAN LITERASI MATEMATIKA SISWA KELAS V SEKOLAH DASAR GUGUS XIV KOTA BENGKULU - Saraseila, Fasadena; Karjiyati, V; Agusdianita, Neza (Universitas Muhammadiyah Bengkulu, 2020)
This study aims to determine the effect of Realistic Mathematics Education models on the ability of mathematics literacy of fifth grade students of the XIV Cluster Elementary School in Bengkulu City. This research is a quantitative research. The method used is quasy experimental with desigen type is the matching only pretest-posttest control group design. The population in this study was the elementary school cluster XIV Bengkulu City. The sampling technique used cluster random sampling. The sample in this study was class V at SDN 42 Bengkulu City as an experimental class and class V at SDN 24 Bengkulu City as a control class. The research instrument used in the form of a test sheet in the form of a description of 4 squestions. Taking the test twice, namely before and after learning takes place in the experimental and control classes. Based on the t-test calculation of the students' posttest results, where tcount= 4.09 and ttable = 2.07. Because tcountttable, it can be concluded that there is a significant difference on the use of realistic mathematics education models on the ability of mathematics literacy of fifth grade students in the XIV group of Bengkulu city.Keywords: Realistic Mathematics Education, Mathematical Literacy Ability